2011
DOI: 10.1136/bmjqs.2009.034587
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of computer-enabled discharge communication interventions: a systematic review

Abstract: Computer-enabled discharge communications appear beneficial with respect to a number of important secondary outcomes. Primary outcomes of mortality and readmission are less commonly reported in this literature and require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…The reviews of Kripalani et al and Wilson et al found deficits in various aspects of DS, for example, timeliness and content [2,9]. Computer-assisted writing and DS transmission seem to be beneficial, according to a review of Motamedi et al [41]. In clinical practice and postgraduate training, however, these reviews are typically of limited value because they do not contain practical recommendations on how to improve the content of DS.…”
Section: Question 2: Guidelines and Reviewsmentioning
confidence: 96%
See 1 more Smart Citation
“…The reviews of Kripalani et al and Wilson et al found deficits in various aspects of DS, for example, timeliness and content [2,9]. Computer-assisted writing and DS transmission seem to be beneficial, according to a review of Motamedi et al [41]. In clinical practice and postgraduate training, however, these reviews are typically of limited value because they do not contain practical recommendations on how to improve the content of DS.…”
Section: Question 2: Guidelines and Reviewsmentioning
confidence: 96%
“…Dictating and typing: Whenever the work conditions permit, DS should be dictated rather than typed by the physician because this process is significantly faster and more efficient [41,55]. The overall quality of a dictated letter tends to be better.…”
Section: Processingmentioning
confidence: 99%
“…Errors in medical documentation are a critical problem that can adversely impact quality of care and patient safety (11)(12)(13)(14)(15). We found nearly 71% of notes contained errors with an average of 1.3 errors per note.…”
Section: Discussionmentioning
confidence: 95%
“…The extensive health informatics infrastructure currently being developed will allow for the more accurate and timely detection of medical errors and the risk factors for such events across the health care continuum. 43 Overall, about three-fifths of the PRINDs that we identified in this study were assessed on the 2008 and 2009 administrations of the MCC QE. Given the key role that licensure exams play in testing PRINDs related to causing and preventing SOCR and avoidable AEs, one could argue that such examinations need to test more PRINDs to better protect the public against suboptimal medical care.…”
Section: Discussionmentioning
confidence: 99%